2015
DOI: 10.1371/journal.pone.0134409
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Inhibitors of Cholinesterase 3 (Ric-3) Expression Promotes Selective Protein Associations with the Human α7-Nicotinic Acetylcholine Receptor Interactome

Abstract: The α7-nicotinic acetylcholine receptor (α7-nAChR) is a ligand-gated ion channel widely expressed in vertebrates and is associated with numerous physiological functions. As transmembrane ion channels, α7-nAChRs need to be expressed on the surface of the plasma membrane to function. The receptor has been reported to associate with proteins involved with receptor biogenesis, modulation of receptor properties, as well as intracellular signaling cascades and some of these associated proteins may affect surface exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 105 publications
(105 reference statements)
1
8
0
Order By: Relevance
“…The activity of GTS-21, NS6740, other α7 silent agonists, and allosteric modulators [1,15,17,32,34,56] in models of inflammatory disease and neuropathic pain appear to be independent of ion channel activation and, rather, depend on activation and modulation of intracellular signal transduction pathways [4,14,26,49,54]. In the case of the α7-mediated control of CAP, the cellular mediators of activity are themselves not even competent for generating nAChR channel currents, and so we must consider the complete receptor protein [50], multiple conformational states, and the complete receptor interactome [29,42] as mediators of the activity.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of GTS-21, NS6740, other α7 silent agonists, and allosteric modulators [1,15,17,32,34,56] in models of inflammatory disease and neuropathic pain appear to be independent of ion channel activation and, rather, depend on activation and modulation of intracellular signal transduction pathways [4,14,26,49,54]. In the case of the α7-mediated control of CAP, the cellular mediators of activity are themselves not even competent for generating nAChR channel currents, and so we must consider the complete receptor protein [50], multiple conformational states, and the complete receptor interactome [29,42] as mediators of the activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications report difficulties showing functional α7nAChR ion channels in macrophages or similar cell types (reviewed in [19] but see [25]). As such, it has been proposed that these cells express metabotropic rather than ionotropic α7nAChRs [26]. We also tested other cell lines ( Figure S1A) and found that SH-SY5Y, not SH-EP1, cells express NACHO.…”
Section: Discussionmentioning
confidence: 74%
“…The same peptide was identified previously in SH-SY5Y samples (not shown) and in transfected SH-EP1 cells, two human neuroblastoma-derived cell models of α 7-nAChR expression. 34 In addition to identifying α 7-nAChRs, GABA A R subunits, recently shown to bind α -bgtx, were identified in both α -bgtx and non- α 7-nAChR, α -bgtx interactomes, but not in the α 7-nAChR interactome (Table 1). 21,35 This observation stresses the importance of controls that are α 7-nAChR-specific when using α -bgtx-affnity immobilization.…”
Section: Resultsmentioning
confidence: 99%